2019
DOI: 10.24875/ric.19002943
|View full text |Cite
|
Sign up to set email alerts
|

Piperacillin/Tazobactam in Continuous Infusion versus Intermittent Infusion in Children with Febrile Neutropenia

Abstract: Background: Febrile neutropenia (FN) is a common complication in children who receive chemotherapy for cancer. Objective: The objective of this study was to evaluate the clinical efficacy of the continuous versus intermittent infusion of piperacillin/ tazobactam (TZP) in febrile neutropenic pediatric patients. Methods: This is a non-blinded randomized controlled clinical trial. Eligible group consisted of hemato-oncological patients with FN who were candidates to receive TZP. Patients were randomized to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…Accepted values for single measurements are between >38.3 °C and >38.5 °C, but certain studies [ 4 ] consider values as low as ≥37.8 °C in their definitions of fever. Multiple readings >/≥38 °C at least one hour after the first reading are also considered to be fever; one study [ 15 ] considered three temperature measurements between 37.5 and 38 °C over 24 h to be fever [ 2 , 4 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Accepted values for single measurements are between >38.3 °C and >38.5 °C, but certain studies [ 4 ] consider values as low as ≥37.8 °C in their definitions of fever. Multiple readings >/≥38 °C at least one hour after the first reading are also considered to be fever; one study [ 15 ] considered three temperature measurements between 37.5 and 38 °C over 24 h to be fever [ 2 , 4 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…When each study was analyzed individually, however, only two of them [ 12 , 24 ] listed Gram-positive bacteria as being the primary pathogen of their MDI, while all the rest described Gram-negative bacteria to be the leading cause of the infections, with Gram-positive pathogens taking up the second place. The third place was occupied by fungi in all but one study [ 14 ], where there were more fungi identified as Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous infusion included a loading dose of 75 mg/kg over 30 min, followed by a 24 h continuous infusion of 300 mg/kg/day. Among 176 episodes assessed, no statistically significant difference was found in fever resolution, clinical cure rate or mortality between the continuous Infusion group and the intermittent administration group, with respectively 16 and 13 cases of treatment failure; one patient in each group died [58].…”
Section: Clinical Outcomementioning
confidence: 87%